Interventional effects of oral microecological agents on perioperative indicators of colorectal cancer: a meta-analysis - Xueyan Wang; Lijun Pan; Feiqing Wang; Fengxi Long; Bing Yang; Dongxin Tang (Frontiers in Oncology, 2023)
PurposeTo investigate the efficacy of the application of microecological agents in patients with perioperative colorectal cancer.MethodsThe seven electronic databases including PubMed, Cochrane Library, Excerpt Medica Database (Embase), Web of Science (WOS), Chinese Biomedical Literature Database (CBM), China National Knowledge Infrastructure (CNKI), and Wan-fang Database were systematically searched for eligible studies from 2000 to February 2023.ResultsA total of 38 randomized controlled clinical trials were included in this study, with a total of 1765 patients in the microecological preparation group and 1769 patients in the control group. All data were analyzed using Review Manager 5.4 and R 4.2.2 software. Meta-analysis showed that in the perioperative period of colorectal cancer, the microecological agents group reduced patients’ adverse drug reactions, improved intestinal flora with Lactobacillus (SMD, 3.0858, [2.0197; 4.1520], p< 0. 0001), Bifidobacterium (SMD, 2.1551, [1.6145; 2.6956], p< 0.0001) and Escherichia coli (SMD, -1.1393, [-1.6247; -0.6538], p< 0.0001); protection of intestinal mucosal barrier function, endotoxin (SMD, -2.6850 [-4.1399; -1.2301], p=0.0003), DAO (SMD, -2.5916, [-3.4694; -1.7137], p<0.0001) and plasma D-lactate (SMD, -5.4726, [-9.8901; -1.0551], p= 0.0152), reduced inflammatory response, IL-6 (SMD, -3.1279 [-5.7706; -0.4852], p=0.0204) and CRP (SMD, -3.9698 [-7.6296; -0.3100], p=0.0335); improved the immune function of the organism, CD4+ (SMD, 1.5817 [1.0818; 2.0817], p< 0.0001), CD4+/CD8+ (SMD, 1.2938 [0.9693; 1.6183] p< 0.0001) and IgG (SMD, 1.1376 [0.2993; 1.9759] p=0.0078), improved short-term clinical efficacy, ORR (RR, 1.5105 [1.2306; 1.8541], p< 0.0001) and DCR (RR, 0.3896 [0.2620; 0.5795], p< 0.0001).ConclusionBy increasing the number of beneficial flora such as Lactobacillus and Bifidobacterium and decreasing the number of harmful flora such as Escherichia coli, the micro-ecological preparation group is beneficial in improving the ecological dysregulation in colorectal cancer patients receiving different treatments in the perioperative period. The microecological preparation group was able to reduce many types of adverse drug reactions, such as infections and gastrointestinal discomfort, compared to the control group. The microecological agents also reduced inflammatory responses, decreased the increase in harmful metabolites, enhanced patients’ immune function, protected intestinal mucosal barrier function, and improved short-term clinical outcomes.Systematic review registrationhttps://inplasy.com/inplasy-2023-4-0051/, identifier INPLASY202340051.